The Romance of Motherhood: Generation and the Literary Text - Labbe, Jacqueline (Romanticism on the Net)

(untitled) (Université de Montréal, 2002)
AbstractThis essay discusses the deployment of maternal imagery in the writings of Charlotte Smith, Mary Wollstonecraft, Mary Robinson, Mary Shelley, and Maria Elizabeth Robinson and situates it in terms of a Romantic-period idealization of the mother. It argues that for authors who were mothers, maternal imagery functioned both to validate and justify their writing, and to communicate a controlled image of themselves to their daughters and their readers. For daughters who both read and wrote, maternal imagery allowed the recreation of the (absent) mother in print. For both, the familial became a metaphor for the literary and a way of rewriting patriarchy, providing an alternative type of inheritance.